STUDI KELAYAKAN EMBUNG SANGUREJO SEBAGAI ASET WISATA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA WONOKERTO, KECAMATAN TURI, KABUPATEN SLEMAN, YOGYAKARTA - Syamsu, Moch. Nur (Kepariwisataan: Jurnal Ilmiah, 2016)
In Indonesia, tourism has become one of the most important sectors of the economy. The government is aware of this so they are trying to develop tourism seriously. Things that can add value to the attractiveness and competitiveness of tourism are the creativity and spirit of society. One of the tourism potential in the form of artificial objects that can be utilized by the community for purposes of irrigation but also as a tourist attraction is embung. Wonokerto is one of the villages in Sleman area that has built an embung, but not yet used it as a tourism asset. Realizing the potential of Embung Sangurejo in Wonokerto Village, a feasibility study of the embung is required. The analysis used in this research is SWOT analysis. This analysis found the way of Embung Sangurejo development as a tourism asset to improve the welfare of the people of Wonokerto Village which is directed at the efforts for more and more tourists coming. In addition, length of stay is increased by creating a variety of tourist attractions, such as rosulan, manakiban, pencak silat, and others. Keywords: Embung, Creativity, Tourism